Corporate Finance in a Digital Green Economy: FinTech's Role in Enabling Sustainable Investment and Funding Models - Regita Natasya Subekti; Judith Tagal G. Sinaga; Valentine Siagian (Community Engagement and Emergence Journal (CEEJ), 2026)
The integration of financial technology (FinTech) with the digital green economy has reshaped banking intermediation, particularly in emerging markets such as Indonesia Stock Exchange. However, empirical evidence regarding their combined influence on sustainable investment remains inconclusive. This study investigates the differential impact of FinTech adoption and digital green economy dynamics on sustainable investment among listed banking firms. It further advances the literature by positioning FinTech and green finance as interdependent mechanisms within Indonesia’s post-pandemic institutional context, rather than as isolated domains. Methods: This research adopts a quantitative design based on 408 firm-year observations of banks listed on the IDX. Multiple linear regression is employed to assess the influence of FinTech and digital green economy on sustainable investment. The analysis is complemented by rigorous classical assumption testing, including normality and multicollinearity diagnostics, to ensure model robustness. Results: The empirical findings demonstrate that FinTech has positive and statistically significant effect on sustainable investment, indicating its effectiveness in enhancing financial intermediation efficiency and transparency. Conversely, the digital green economy variable exhibits a negative coefficient, suggesting the presence of transitional inefficiencies, structural rigidities, and initial adjustment costs associated with early-stage implementation. Conclusion: The results highlight an asymmetric digital-green relationship: FinTech acts as an immediate catalyst for sustainable investment, while broader digital green transformation introduces short-term constraints that may hinder investment outcomes. These findings imply technological advancement alone is insufficient without institutional and structural alignment. Therefore, banks should emphasize targeted FinTech implementation to optimize sustainable investment performance within emerging digital green frameworks.